Ultra-low-dose lung multidetector computed tomography in children – Approaching 0.2 millisievert. Issue 139 (June 2021) - Tschauner, Sebastian; Zellner, Michael; Pistorius, Sarah; Gnannt, Ralph; Schraner, Thomas; Kellenberger, Christian J.
Highlights: Sufficient-quality paediatric lung CT can be achieved at effective radiation doses of 0.1 to 0.3 mSv on contemporary MDCT. Localizer radiograph doses increasingly account for substantial portions of a total scan's doses and should be optimized. Rapid progress in scanner technique emphasizes the necessity to perform paediatric lung CTs on contemporary equipment. Abstract: Purpose: To compare objective and subjective parameters in image quality and radiation dose of two MDCTs (helical 64 detector CT vs. axial 256 detector CT) in paediatric lung CT. Methods: Radiation dose and image quality were compared between non-enhanced lung CT from a helical 64-slice multidetector CT (MDCT 1) and a 256-slice scanner (MDCT 2) with axial wide-cone acquisition and using deep learning image reconstruction. In 23 size-matched paediatric studies (age 2–18 years) from each scanner, the radiation exposure, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), image sharpness and delineation of small airways were assessed. Subjective image quality was rated by 6 paediatric radiologists. Results: While MDCT 2 provided higher SNR and CNR, subjective image quality was not significantly different between studies from both scanners. Radiation exposure was lower in studies from MDCT 2 (CTDIvol 0.26 ± 0.14 mGy, effective dose 0.23 ± 0.11 mSv) than from MDCT 1 (CTDIvol 0.96 ± 0.52 mGy, effective dose 1.13 ± 0.58 mSv), p < 0.001. Despite lower radiation dose for the scout images, the relative scout-scan-ratio increased from 2.64 ± 1.42 % in MDCT 1 to 6.60 ± 5.03 % in MDCT 2 (p = 0.001). Conclusions: By using latest scanner technology effective radiation dose can be reduced to 0.1−0.3 mSv for lung CT in children without compromising image quality. Scout image dose increasingly accounts for substantial portions of the total scan dose and needs to be optimized. In children CT should be performed on state-of-the-art MDCT scanners with size-adapted exposure protocols and iterative reconstruction.